Stress, Anxiety, and Depression among School Students A Cross-sectional Study - Sarif, MD Nawaz; Vandana, (JOURNAL OF INDIAN EDUCATION, 2022)
The issues of psychiatric disorders and negative emotions are highly prevalent among school-going students. The current study investigated the prevalence of stress, anxiety, and depression among students in North-East India and found its significant difference and vertical pattern across grades. Using DASS-42, data collection was done from a non-representative sample of 192 students of VII, VIII, and IX grades. Findings showed a high prevalence of psychiatric disorders among sampled students. It was found that anxiety (65.9 per cent) was much more prevalent among students, followed by depression (45.97 per cent) and stress (34.09 per cent). It was identified that the prevalence of stress, anxiety, and depression was higher among IX students (44.54 per cent, 71.43 per cent and 53.78 per cent), followed by the VIII (36.11 per cent, 66.67 per cent and 50 per cent) and VII grades (21.62 per cent, 59.64 per cent and 34.14 per cent). Besides, it also revealed a significant mean difference in students’ anxiety, X2(2) =7.149, p=0.028, and depression, X2(2) =9.666, p=0.008 with respect to their grades, while no significant mean difference was recorded in stress, X2(2) =2.076, p=0.354. From the findings, it was inferred that mental health issues among school-going students increase with an increase in their level of school education, which raises serious concerns for stakeholders.